A systems thinking approach to address the complex issue of plastic surgery in South Korea. (2015) - Nguyen, Nam C.; Bosch, Ockie J.H.; Banson, Kwamina E.; Ting, Odelia Ling Jia; Xuan, Jemaine G.C.; Hui, Michelle S.X.; Lim, Zoey
Bodily shape and facial appearances which do not remain the same with aging varies across culture and continents and these are impacted by racism, class prejudice and ableism. As a result many people with less self-esteem resort to varying beauty therapy including plastic surgery. More than 5.8 million enhancements with photos of celebrities to emulate them are done by people every year in Asia. But people who are dissatisfied request repeat procedures or experience depression and adjustment problems, social isolation, family problems, self-destructive behaviours and anger toward the surgeon and staffs. To date, no solution has been put into place to reduce the number of plastic surgeries. This study therefore uses a systems thinking approach to identify the key variables that are affecting this trend. Casual loop diagrams developed reveal and foster integrated planning for governments to intervene the lustic interest in plastic surgery to minimise negative consequences and reduce impersonations and the wrong motives such as; undergoing plastic surgery to achieve success in life. The Bayesian models developed will help decision makers anticipate the long-term consequences of their decisions and actions, as well as avoid the unintended consequences of plastic surgery on the health system.